Assessment of psychological distress among nursing undergraduate students in Malaysia - Radeef Al-Ani, Ali Sabri; Faisal, Ghasak Ghazi; Al-Kubaisi, Muna Khaleel Dheyab (Seventh Sense Research Group, 2019)
Introduction: Studies among undergraduate students in Malaysia have assessed the impact of stressors on the mental health of students. Nursing students are subjected to a variety of stressors during their study. Severe and prolonged stressors may lead to psychological distress which may affect students’ academic performance, physical health and quality of life. Therefore, this study aimed to determine the rate of psychological distress and its relationship with stressors faced by the students. Methodology:A sample of 174 nursing students from International Islamic University Malaysia participated in this study. The psychological distress was assessed using the 12-item General Health Questionnaire. The sources of stressors were identified by giving the students a list of the most possible source of stressors which were chosen depending on previous studies, and then the severity of stressors and their relationship with psychological distress were assessed. Results: The prevalence of psychological distress was 31.6%. No significant differences between the gender and age of students in relation to psychological distress. Regarding the source of stressors, the top five stressors decided by the students were fear of failing, examination and grades, study pressure and obligations, fear of unemployment after graduation andacademic overload. Conclusion: psychological distress is present among nursing students which require early intervention. Academic and psychological factors can be considered as sources of stressors that may precipitate emotional disturbances among the nursing students.